Paper based narrations: : a study of the types of narrative texts used in early childhood education classrooms in Madrid - Herranz Llácer, Cristina V.; Segovia Gordillo, Ana (Huarte de San Juan. Filología y Didáctica de la Lengua, 2022)
The aim of this article id to carried out a study about the different tales that are used in classrooms from 0 to 6 years old in Spain. The objective was to know the type of narrative text which are used according to the academic year, the type of centre (public, private, or subsided), and the perception of the usefulness of the academic education of teachers. The research has been developed through a qualitative associative study based on an online survey of 111 teachers. The main results show how teachers generally perceive that their academic education has influenced the use of certain types of tales such as classic stories. On the other hand, the specific education that teachers have about Children’s and Youth Literature needs to be reinforced within the different study plans.